Line strength analysis of the 12CD4 infrared spectra in the pentad region; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 341 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Nikolaeva N. I. Natalya Ivanovna; Guan Xinran; Sydow C. Christian; Bauerekker Z. Kh. Zigurd Khermann (2025, 2025)
Title screen